Nanoindentation Investigation of Chloride-Induced Stress Corrosion Crack Propagation in an Austenitic Stainless Steel Weld - Haozheng J. Qu; Janelle P. Wharry (Metals, 2022)
Transgranular chloride-induced stress corrosion cracking (TGCISCC) is a mounting concern for the safety and longevity of arc welds on austenitic stainless steel (AuSS) nuclear waste storage canisters. Recent studies have shown the key role of crystallography in the susceptibility and propagation of TGCISCC in SS weldments. Given that crystallography underlies mechanical heterogeneities, the mechanical-crystallographic relationship during TGCISCC growth must be understood. In this study, welded SS 304L coupons are loaded in four-point bend fixtures and then boiled in magnesium chloride to initiate TGCISCC. Nanoindentation mapping is paired with scanning electron microscopy (SEM) electron backscatter diffraction (EBSD) to understand the correlation between grain orientation, grain boundaries, and hardening from TGCISCC propagation. The nanoindentation hardness of individual grains is found to not be a controlling factor for TGCISCC propagation. However, intragranular hardness is generally highest immediately around the crack due to localized strain hardening at the crack tip. This work shows that nanoindentation techniques can be useful in understanding CISCC behaviors when paired with electron microscopy.